2021
DOI: 10.1369/00221554211031678
|View full text |Cite
|
Sign up to set email alerts
|

SPM Receptor Expression and Localization in Irradiated Salivary Glands

Abstract: Radiation therapy–mediated salivary gland destruction is characterized by increased inflammatory cell infiltration and fibrosis, both of which ultimately lead to salivary gland hypofunction. However, current treatments (e.g., artificial saliva and sialagogues) only promote temporary relief of symptoms. As such, developing alternative measures against radiation damage is critical for restoring salivary gland structure and function. One promising option for managing radiation therapy–mediated damage in salivary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Studies of SPM and AT forms within the SG have been largely confined to a single resolvin (AT-RvD1, one of many in the resolvin family) that has shown promise for treating hyposalivation. Specifically, previous studies demonstrated that AT-RvD1 reduces inflammation and restores tissue integrity in SG cells ( 88 91 ), AT-RvD1 biosynthetic and signaling pathways are active in mice and human SG ( 89 93 ), the progression of the SS-like features in NOD/ShiLtJ mice is halted using AT-RvD1, with mice treated systemically prior to disease onset displaying downregulation of pro-inflammatory cytokines, upregulation of anti-inflammatory molecules and intact saliva production ( 44 , 94 ), similar results are obtained with AT-RvD1 treatment at disease onset and lack of the RvD1 receptor ALX/FPR2 leads to impaired innate ( 42 ) and adaptive immunity ( 33 ) in mouse submandibular glands (SMG), with such results derived within the SG being consistent with studies obtained using the full range of SPM in other organs ( 95 105 ). Despite the promise shown by SPM in general and AT-RvD1 in particular for treating SS, there are several obstacles that must be overcome for this treatment to be implemented in oral medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of SPM and AT forms within the SG have been largely confined to a single resolvin (AT-RvD1, one of many in the resolvin family) that has shown promise for treating hyposalivation. Specifically, previous studies demonstrated that AT-RvD1 reduces inflammation and restores tissue integrity in SG cells ( 88 91 ), AT-RvD1 biosynthetic and signaling pathways are active in mice and human SG ( 89 93 ), the progression of the SS-like features in NOD/ShiLtJ mice is halted using AT-RvD1, with mice treated systemically prior to disease onset displaying downregulation of pro-inflammatory cytokines, upregulation of anti-inflammatory molecules and intact saliva production ( 44 , 94 ), similar results are obtained with AT-RvD1 treatment at disease onset and lack of the RvD1 receptor ALX/FPR2 leads to impaired innate ( 42 ) and adaptive immunity ( 33 ) in mouse submandibular glands (SMG), with such results derived within the SG being consistent with studies obtained using the full range of SPM in other organs ( 95 105 ). Despite the promise shown by SPM in general and AT-RvD1 in particular for treating SS, there are several obstacles that must be overcome for this treatment to be implemented in oral medicine.…”
Section: Introductionmentioning
confidence: 99%